Deep convolutional neural networks-based scatterer density and resolution estimators in optical coherence tomography: erratum - Thitiya Seesan; Ibrahim Abd El-Sadek; Pradipta Mukherjee; Lida Zhu; Kensuke Oikawa; Arata Miyazawa; Larina Tzu-Wei Shen; Satoshi Matsusaka; Prathan Buranasiri; Shuichi Makita; Yoshiaki Yasuno (My University, 2024)
Errata are presented to correct the inconsistencies between the values and their units displayed in the figures and the texts in our published manuscript [ Biomed. Opt. Express 13 , 168 ( 2022 ) 10.1364/BOE.443343 ]. The errors were caused by the unit presentation of the original manuscript, and hence, it does not affect the main results and the conclusion.
Keywords: Optical Tomography; Optical Coherence Tomography Applications